Solve the system using elimination. 3x – y = 28 3x + y = 14

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Solve the system using elimination. 3x – y = 28 3x + y = 14

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

(8, –4) (–7, 7) (7, –7) (–4, 8)
hint: add the two equations together
start with the x's 3x + 3x = ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

3+3=6 28+14=42
almost 3 + 3 = 6 3x + 3x = ___ fill in the blank
6x?
good! now go to the y's -y + y = ?
0?
good! now we have 6x = 42 x = ___ fill in the blank
do i add those together?
nope, just find x
6x = 42 what does x = ?
7
good! x = 7, so we look for the answer choice with an x-coordinate of 7 the only possibility is (7,-7)
yeah
can u help me with -5x+y=-5 -4x+2y=2
hint: multiply the first equation by 2 first
ok 10
nope -5x*2 = ?
-10?
don't forget the x
ok, the way I wrote it was a bit vague, but I meant (-5)*(2)*x = ?
-10x
what do I do next?
2*y = ?
whats y?
-5x + y = -5 ----multiply by -2 -4x + 2y = 2 ------------ 10x - 2y = 10 (result of multiplying by -2) -4x + 2y = 2 ------------add 6x = 12 -- divide by 6 on both sides x = 2 now sub 2 in for x in one of the original equations and find y. questions ?
-6?
-4*2+2=-6
-5x + y = -5 -5(2) + y = -5 -10 + y = -5 y = -5 + 10 y = 5 check... -4x + 2y = 2 -4(2) + 2(5) = 2 -8 + 10 = 2 2 = 2 (correct) so x = 2 and y = 5
someone told me 2,5 wasnt the right answer..
plug it into the original equations to check... -4x + 2y = 2 -5x + y = -5 -4(2) + 2(5) = 2 -5(2) + 5 = -5 -8 + 10 = 2 -10 + 5 = -5 2 = 2 (correct) 5 = 5 (correct) (2,5) is the solution because it checks out in both equations as correct
Thank You

Not the answer you are looking for?

Search for more explanations.

Ask your own question